Kinematics of the hip and body center of mass in front crawl - Fernandes, R. J.; Ribeiro, J.; Figueiredo, P.; Seifert, L.; Vilas-Boas, J. P. (Journal of Human Kinetics, 2012)
The kinematic profiles of the hip and center of mass in front crawl swimming were compared to quantify the error of using a fixed body point to assess intracyclic velocity variations at moderate intensity exercise. The practical goal was to provide a useful tool, easy and fast to assess, and to use as feedback, for assessing swimming efficiency. Sixteen swimmers performed an intermittent incremental protocol that allowed assessing the individual anaerobic threshold velocity. One complete stroke cycle was analysed at the step intensity corresponding to each swimmer's anaerobic threshold. The subjects were videotaped in the sagittal plane using a double camera set-up for two-dimensional kinematical analyses. The hip and the center of mass presented similar mean velocity and displacement values, being highly related to both parameters. However, the hip reflects the center of mass forward velocity and horizontal displacement with 7.54% and 3.24% associated error, respectively. Differences between hip and center of mass were observed for intracyclic velocity variations (0.19±0.05 and 0.25±0.08, respectively, for a p